Feasibility of investigating methylphenidate for the treatment of sarcoidosis-associated fatigue (the FaST-MP study): a double-blind, parallel-arm randomised feasibility trial. Issue 1 (21st May 2021) - Atkins, Christopher; Jones, Andy; Clark, Allan B; Stockl, Andrea; Fordham, Richard; Wilson, Andrew M
Abstract : Introduction: Sarcoidosis-associated fatigue (SAF) is a common clinical problem with limited treatment options. This study was undertaken to determine the feasibility of performing a definitive trial to determine the clinical efficacy methylphenidate in SAF. Methods: This was a parallel-arm, double-blind, placebo-controlled randomised controlled feasibility trial enrolling sarcoidosis patients reporting significant fatigue. Patients with a Fatigue Assessment Scale score of more than 21 were randomised to receive up to either 10 mg two times per day methylphenidate or identical placebo capsules two times per day, in a dose escalation fashion, for up to 24 weeks. Outcomes included number of participants eligible and willing to participate, withdrawal rates, adherence rates and ability to maintain blinding. Results: Of 385 patients screened, 56 (14.5%) were eligible and 23 (41% of eligible patients) were randomised. No withdrawals occurred. One participant in the methylphenidate arm discontinued study medications due to chest pain. The side effect profile was not different between the groups. Median medication adherence rates were 98% and 99% in the methylphenidate and placebo arms, respectively. A greater proportion of participants receiving methylphenidate predicted their allocated treatment while blinded compared with those receiving placebo (93.3% vs 57.1%). The investigator could not predict the treatment allocation. Both groups showed clinically meaningful improvements in fatigue from baseline, although no between-group difference was seen. Conclusions: The data support the feasibility of performing a double-blind parallel trial powered to determine the clinical efficacy of methylphenidate for SAF, however, a multicentre study will be required. Trial registration number: NCT02643732 .